A Hardware Platform for Utilizing the TV Bands with a Wi-Fi Radio - Narlanka, Srihari; Chandra, Ranveer; Bahl, Victor; Ferrell, Ian (IEEE LANMAN, 2007)
The Federal Communications Commission (FCC) is currently exploring the use of TV bands for unlicensed communication. This step has sparked significant interest in the research and corporate community as it opens up new possibilities for high speed and long range wireless communication. In this paper, we present the design and implementation of a complete system that can detect the presence of TV signals, and perform high-speed data communication in an available TV band without interfering with neighboring TV bands. To the best of our knowledge, this is the first known system with all the above capabilities.